2016
DOI: 10.4172/1745-7580.10000122
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns, Foods, Nutrients and Chronic Inflammatory Disorders

Abstract: The World Health Organization (WHO) recognizes that diet plays an important role in the prevention of several non-infectious diseases. Unhealthy diets that include high intake of red and processed meat, sweets and desserts, potatoes, French fries, and refined grains) is associated with high plasma inflammatory biomarkers and a greater risk of cardiovascular disease (CVD), type 2 diabetes (T2D), cancer and other chronic diseases. On the other hand, prudent dietary patterns such as Mediterranean diet as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 131 publications
(114 reference statements)
0
12
0
Order By: Relevance
“…In contrast, examples of unhealthy dietary patterns include Western diets and high fat and meat diets (11). It is thought that diets high in refined starches, saturated fats, trans-fatty acids, and sodium, and lower in whole grains, fruit, vegetables, omega-3 fatty acids, and fiber may heighten the inflammatory response (12). As elevations in inflammatory markers have been suggested as a biomarker for the incidence of CKD (13), a dietary approach which lowers inflammatory markers and dietary acid load may be important for reducing the incidence of CKD.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, examples of unhealthy dietary patterns include Western diets and high fat and meat diets (11). It is thought that diets high in refined starches, saturated fats, trans-fatty acids, and sodium, and lower in whole grains, fruit, vegetables, omega-3 fatty acids, and fiber may heighten the inflammatory response (12). As elevations in inflammatory markers have been suggested as a biomarker for the incidence of CKD (13), a dietary approach which lowers inflammatory markers and dietary acid load may be important for reducing the incidence of CKD.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of evidence linking diet with the immune system functioning and the modulation of the inflammatory response [ 10 , 11 ]. An unhealthy diet that is high in saturated fats and refined sugars seems to be one of the main factors implicated in the development of obesity and other NCDs [ 10 ], while a diet rich in fruit, vegetables, extra virgin olive oil, legumes, whole grains, fish, nuts, cocoa, coffee, tea, and red wine, similar to the Mediterranean diet, has demonstrated beneficial effects on cardiometabolic risk reduction [ 12 ]. The abovementioned food items contain various bioactive components that exhibit anti-inflammatory activity [ 12 , 13 ], and if consumed as a dietary pattern, it could be considered an anti-inflammatory diet, although currently, there is still no single, comprehensive, universally accepted definition of such a diet.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation may be favored by several factors such as age, obesity, smoking, stress, sleep disorders and/or diet [4]. Indeed, previous studies have consistently demonstrated that several dietary factors influence chronic inflammation [5][6][7]. Diets with high omega-3 intake, low saturated and trans fatty acids intake, and high intake of fruits, vegetables, nuts and whole grains have been associated with a lower generation of inflammation [8].…”
Section: Introductionmentioning
confidence: 99%